Antimicrobial Properties Of Endophytic Fungi Isolated From Medicinal Plant Camellia Sinesis - NAMEIRAKPAM NIRJANTA DEVI,; FEMINA WAHAB, (International Journal of Pharma and Bio Sciences, 2012)
The purpose of this work was to evaluate the antimicrobial potential of endophytic fungi isolated from leaves of Camellia sinesis plant. Many endophytes were isolated by using potato dextrose agar medium. In that one potent strain was taken for further study. The fungal culture was extracted with ethyl acetate and used as a crude extract for checking antimicrobial activities. The crude fungal extract showed different inhibitory activity against all pathogens. It showed significant activity against Pseudomonas sp. The fungal strain was identified as Penicillium sp. through 18S ribosome RNA sequence analysis. The Penicillium sp. showed 100% gene sequence similarities with Penicillium funiculosumstrainTS08 and Penicillium sp.12-2018S. The sequence of identified strain was submitted in NCBI and obtained accession number HQ214674 with name Penicillium sp. pr NN-2010. The bioactive compounds responsible for antibacterial activity were identified by GC-MS and NMR. The major compound present in crude extract was identified as 3-(3-azidopropyl)-1H-indene (15.39%) and 3-Cyano-1,2-dimethylindole. In Nuclear magnetic resonance analysis most of the peaks range were between the aromatic groups. These results indicate that the bioactive metabolites isolated from fungal Penicillium sp.could be promising source as antibacterial agents.